Pengaruh Cekaman Aluminium Terhadap Pertumbuhan Tanaman Jagung Pada Kultur Air - sholeha sholeha; Dr. Tantri Palupi, SP., M. Si Dr. Tantri Palupi, SP., M. Si; Ahmad Mulyadi, S. Si, M. Si Ahmad Mulyadi, S. Si, M. Si (Jurnal Sains Pertanian Equator, 2016)
ABSTRACT Indonesia has the opportunity to be suppliers of corns in the world, but agricultural land is used less and less. The other alternative to make agriculture still running is to use marginal lands as an extension of the land, but it has some obstacles and one of the obstacle is about solubility levels of  aluminum mineral (Al) and iron (Fe) is still high. So that in order to make the land can be planted we have to choose corns varieties that can grow optimally on marginal lands. To obtain corns varieties which is suitable to be cultivated on marginal land, it can be selected in the culture medium of water, because the results can be obtained in a short time. This study aims to determine the level of tolerance of different varieties of corn plants through stress of Al. This research was conducted in the Greenhouse Faculty of Agriculture, Tanjungpura University, from March to May 2016. Using the method of field experiments in the form of a pattern factorial randomized group design consist of two factors, stress of Al consists of 5 levels: a0 (without Al), a1 (0.1 mM Al), a2 (0.2 mM Al), a3 (0.4 mM Al), a4 (0.8 mM Al) and varieties consists of 3 levels: v1 (Sukmaraga), v2 (Local) and v3 (Bima7). The variables were observed in this research include Al poisoning symptoms,height of plant, the dry weight of the heading  and the dry weight of root. The results of this research indicated that varieties of Sukmaraga and Local were resistant of poisoning on concentration of 0.1 mM and 0.2 mM Al Al. Bima7 variety was resistant of  poisoning Al on concentration of 0.1 mM Al.